Self-association and conformational variation of NS5A domain 1 of hepatitis C virus - Beldar, Serap (2020)
Direct-acting antivirals (DAAs) targeting the non-structural 5A (NS5A) protein of the hepatitis C virus (HCV) are crucial drugs that have shown exceptional clinical success in patients. However, their mode of action (MoA) remains unclear, and drug-resistant HCV strains are rapidly emerging. It is critical to characterize the behaviour of the NS5A protein in solution, which can facilitate the development of new classes of inhibitors or improve the efficacy of the currently available DAAs. Using biophysical methods, including dynamic light scattering, size exclusion chromatography and chemical cross-linking experiments, we showed that the NS5A domain 1 from genotypes 1b and 1a of the HCV intrinsically self-associated and existed as a heterogeneous mixture in solution. Interestingly, the NS5A domain 1 from genotypes 1b and 1a exhibited different dynamic equilibria of monomers to higher-order structures. Using small-angle X-ray scattering, we studied the structural dynamics of the various states of the NS5A domain 1 in solution. We also tested the effect of daclatasvir (DCV), the most prominent DAA, on self-association of the wild and DCV-resistant mutant (Y93H) NS5A domain 1 proteins, and demonstrated that DCV induced the formation of large and irreversible protein aggregates that eventually precipitated out. This study highlights the conformational variability of the NS5A domain 1 of HCV, which may be an intrinsic structural behaviour of the HCV NS5A domain 1 in solution.